Da fragmentação ao bonde: as transformações sociais das dinâmicas criminais em um bairro da Grande São Luís – MA - Lopes, Thiago Brandão (2022)
The present work is the result of an ethnographic research, "up close and from within", in a neighborhood of Greater São Luís - MA. With the objective is to analyze the social transformations of crime between a regime of open rivalries between criminal groups to a regime of alliances where there is a sharing of senses of action between people willing to carry out illicit practices. It examines, therefore, the transition from a fragmented scenario where there are several groups that practice illicit acts and that have their own repertoires of action closely linked to the territory where they operate, to a much more complex arrangement, composed of the domain of a single criminal collective known as “Bonde”, which, in addition to structuring an intricate relational dynamic between prison and street, in the last decade has started to impose itself throughout the researched territory through the sharing of the same “normative regime”, which has guaranteed to this territory a “pax factional” of relations between “bandits”. This pax was achieved through norms of coexistence established by an institution of self-regulation and self-determination of the “world of crime”.